Stress The Stress - NITU BANSAL; SACHDEV YADAV (International Journal of Pharma and Bio Sciences, 2010)
"Nothing gives one person so much advantage over another as to remain always cool and unruffled under all circumstances." Thomas Jefferson Stress is a biological term which refers to the consequences of the failure of a human or animal body to respond appropriately to emotional or physical threats to the organism, whether actual or imagined. It is "the autonomic response to environmental stimulus.” Stress is a feeling that’s created when we react to particular events. It’s the body’s way of rising to a challenge and preparing to meet a tough situation with focus, strength, stamina, and heightened alertness. A condition or circumstance (not always adverse), which can disturb the normal physical and mental health of an individual. In medical parlance ’stress’ is defined as “a perturbation of the body’s homeostasis.”It is a "nonspecific response of the body to a demand."